DISTINCTIVE FEATURES OF THE SOCIAL STRUCTURE OF CORRUPTION RELATIONS IN MODERN SOCIETIES - Turdikulov Sh (Galaxy International Interdisciplinary Research Journal, 2023)
Corruption is a complex social phenomenon, to which it is quite complicated to find a logically clear and satisfying definition for everyone. To understand the essence of this phenomenon, first of all, in the history of human thought, the need for an analysis of the formation and evolution of the concept of “corruption”, as well as the study of the features of its structure in modern societies, is studied.